Trends of adverse pregnancy outcomes and its determinants in Arba Minch Zuria and Gacho Baba Woredas from 2018 to 2022: Analysis of health and demographic surveillance data. - Zeleke Gebru; Fekadeselassie Berhe; Shitaye Shibiru; Bereket Honja; Mesfin Kote; Alazr Baharu; Tadesse Awoke (PLoS ONE)
Introduction Many family members and the expectant mother view pregnancy as a time of joyful anticipation. However, it can also bring about a range of issues that may pose serious and potentially life-threatening risks for both the mother and the unborn child. Adverse pregnancy outcomes are an alarming public issue in different parts of the world and have a seriously harmful influence on both their health and well-being. Nevertheless, less is known about trends and determinates of adverse pregnancy outcomes in the Arba Minch zuria and Gacho Baba districts in southern Ethiopia. Therefore, this study aimed to fill these gaps in the study setting. Methods An open, dynamic cohort study design was employed among 8885 pregnancies from 2018 to 2022, health and demographic surveillance data were involved. Data to be collected at Arba Minch Health and Demographic Surveillance Site (HDSS) using a structured questionnaire. A log-binomial regression model was used to identify determinates. A P-value of less than 0.05 was considered to declare a statistically significant association. Results In this study, the overall adverse pregnancy outcomes were 8.89 per 1000 live births [95%CI: 6.93, 10.84]. The stillbirth and abortion rates were 5.74 per 1000 live births (95%CI: 4.36, 7.54) and 3.15 per 1000 live births [95%CI: 1.97, 4.02], respectively. The trends of adverse pregnancy outcomes showed 11.1/1000 in 2018 and 14.1/1000 in 2022. Age > 34 years old (aPPR = 2.93, 95%CI: 1.67, 5.17), antenatal care (aPPR = 0.52, 95%CI: 0.33, 0.83), and history of pregnancy loss (aPPR = 2.68, 95%CI: 1.36, 5.29) were identified as determinates for adverse pregnancy outcomes. Conclusion The prevalence of adverse pregnancy outcomes is still high, and trends vary from time to time. As such, attention is needed for the women who had a previous history of pregnancy loss, and addressing those determinants could potentially reduce the rates of stillbirths and abortions, ultimately promoting healthier pregnancies and better pregnancy outcomes.